Analysis of Energy Storage Device in Hydro-Thermal Power Systems Using Fuzzy Logic Controller - Shanmugasundaram, V.; ., . (International Journal of Engineering and Technology, 2018)
This work presents the Automatic generation control in an interconnected hydro-thermal power system to stabilize the frequency oscillations due to load changes. Advantage of facts devices are utilized here to improve the stability of the system. Thyristor controlled phase shifter (TCPS) is added in the tie line whose input is the area control error. The output of the phase shifter is the change in phase angle based on the error. The TCPS-RFB (Redox flow battery) and TCPS - SMES (Superconducting magnetic energy storage) combinations are compared against each other in terms of peak overshoot and settling time. The results proves that SMES is most effective than RFB. Then the LFC of hydrothermal plant with TCPS in tie line and SMES in one area is analyzed with different controllers like P, PI, PID and Fuzzy logic controller to find the best controller for these specific applications. The criterion for comparison remains to be the same. And finally fuzzy logic controller is found to best among the ones under consideration.Â Â